2014
DOI: 10.3346/jkms.2014.29.12.1688
|View full text |Cite
|
Sign up to set email alerts
|

Interval from Prostate Biopsy to Radical Prostatectomy Does Not Affect Immediate Operative Outcomes for Open or Minimally Invasive Approach

Abstract: Traditionally, urologists recommend an interval of at least 4 weeks after prostate biopsy before radical prostatectomy. The aim of our study was to evaluate whether the interval from prostate biopsy to radical prostatectomy affects immediate operative outcomes, with a focus on differences in surgical approach. The study population of 1,848 radical prostatectomy patients was divided into two groups according to the surgical approach: open or minimally invasive. Open group included perineal and retropubic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…In present study, we also analyzed other parameters may related to the perioperative outcomes, we found that higher BMI was associated with longer OT which consistent with previous studies, [ 10 , 25 , 26 ] higher PSA level before surgery was associated with higher drainage and longer hospital stay. Our experience suggested that this reflects the higher complexity of RALP in patients with higher BMI or PSA level.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In present study, we also analyzed other parameters may related to the perioperative outcomes, we found that higher BMI was associated with longer OT which consistent with previous studies, [ 10 , 25 , 26 ] higher PSA level before surgery was associated with higher drainage and longer hospital stay. Our experience suggested that this reflects the higher complexity of RALP in patients with higher BMI or PSA level.…”
Section: Discussionsupporting
confidence: 90%
“…[ 9 ] Park et al also reported that biopsy-to-surgery interval did not affect the perioperative outcomes, including the surgical margin, OT or EBL in open, laparoscopic, and robotic approach. [ 10 ] Another large retrospective study carried out by Jo et al has produced similar findings, [ 7 ] they have even found that surgery late after biopsy (after 6 weeks) associated with an increased OT [ 7 ] which may result from the processed inflammation. In fact, most studies supported the opinion that the interval between the biopsy and surgery was not related to the perioperative outcomes even in open prostatectomy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, the impact of time interval between biopsy and RP has not been well established (49). While some observations have suggested early RP is associated with more overall complications and a greater risk of blood transfusion (8), others have found disparate results (5, 7, 9). Herein, we assess the impact of time from biopsy to surgery on complications, functional, and oncologic outcomes following radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Delaying cystectomy for MIBC by 90 days may cause an increase of the pN + rate [19], a decrease of the overall survival and progression-free survival [20,21]. High risk prostate cancer biochemical recurrence rates may be higher in patients if definitive treatments are delayed, but there is not a clear cut-off time for this treatment benefit [22,23,24]. It has also been observed that a 3-months delay to surgery for UTUC inevitably leads to disease progression [25].…”
Section: Discussionmentioning
confidence: 99%